Evaluation of the Effect of Pot Size and Time of Sowing on the Production of Pinus caribaea Var. Hondurensis Seedlings - Kariyappa, G. S.; Amanulla, B. K. Mohamed; Torvi, R. K. (Indian Forester, 1997)
A nursery trial of Pinus caribaea var. hondurensis with 3 pot sizes and 4 dates of sowing was conducted in the year 1992/1993. Results of the trial have indicated that growth parameters viz. shoot length, root length and root collar diameter etc. varied considerably with different pot sizes and time of sowing. A nursery period of about five months was found optimum for production of a planting stock of 25-30 cm height with pot size of 10 cm Ã— 15 cm.